Leachate migration path estimations and groundwater quality analysis near a solid waste dumping site at Kampong Kelichap, Batu Pahat - Jalil, Mas Rahayu (2004)
The impact of Kampong Kelichap solid waste dumping site on groundwater of an unconfined aquifer was investigated. The investigation involved the analysis of groundwater quality and the estimations of leachate or contaminants movement which included the flow direction and velocity. The leachate or contaminants movement were assumed to be similar to the groundwater movement in the study area. Groundwater level and water quality were monitored from August of 2003 to June of 2004 in nine wells (SI to S9) located upstream and downstream of the study area. The measured water quality parameters were pH, temperature, turbidity, conductivity, dissolved oxygen (DO), total dissolved solids (TDS), ammonia nitrogen (NH3-N), sulfate, biochemical oxygen demand (BOD5), and chemical oxygen demand (COD). Contaminants concentration distribution in groundwater has been mapped or contoured using geostatistical analysis. Groundwater and contaminant movement or flow characteristics were estimated using water table contours, correlation surface analysis, and numerical models. The numerical modeling was conducted by using MODFLOW in conjunction with MODPATH and MT3D. Field and laboratory results showed high concentrations of conductivity, COD, NH3 -N and TDS in the downstream groundwater. Field measurements, laboratory analyses, and simulated models showed similar results in which the contaminated wells were S3, S4, S5, and S6. Conductivity, COD, and NH3-N concentration contours suggested the dumping site as the main source of groundwater contamination in the study area. The changes in the patterns on COD concentration contours, the water table contours, the correlation surface analysis, and the numerical models showed that the contaminants and groundwater were traveling mainly toward the southwestern boundary with an average direction of 196 °, 199.5 °, 242.7 °, and 228.4°, respectively, as measured clockwise from the north. The estimated contaminated groundwater velocities from the correlation analysis and numerical model were ranging from 315.5 to 359 m/yr and 174 to 284 m/yr, respectively.